On Convergence of General Gamma Type Operators (Analysis in Theory and Applications, 2011)
The present paper deals with the new type of Gamma operators, here we estimate the rate of pointwise convergence of these new Gamma type operators $M_{n,k}$ for functions of bounded variation, by using some techniques of probability theory.
Keywords: rate of convergence; gamma operator; bounded variation; total variation.